30ft급 요트 선체 주위의 점성유동 해석 - 지혜련(Hye-Ryoun Chi); 김우전(Wu-Joan Kim); 박종환(Jong-Hwan Park) (大韓造船學會 論文集, 2007)
Turbulent flows around a sailing yacht hull were calculated using CFD technique. Grid system was generated by using Gridgen package and Fluent package was used to calculate flows around a 30ft-class yacht hull designed by MOERI. The drafts at starboard and port sides of a yacht. when the hull was heeled, were determined by adjusting the same displacement in the generated grid system. Pressure distribution on the sailing yacht hull was obtained and the changes of drag and side force by heel and leeway variation were shown. The flow calculations have been carried out both with and without free surface, and keel and rudder were included for both cases. It was found that the calculated results with free surface gives better agreement with experiments than those without free surface, although there are still a room for the improvement in correct prediction of forces.